Pengaruh Lembar Kerja Peserta Didik (Lkpd) Puzzle Matematika Terhadap Keaktifan Belajar Peserta Didik Kelas II Sekolah Dasar - Putri, Rahma Kurnia; Anggraeni, Rizky; Salsabila, Siti; Bela, Yuan Devina; Fajrudin, Lili (LPPM Universitas Bina Bangsa, 2025)
The low learning activeness of students in mathematics at the elementary school level is a fundamental problem triggered by the abstract nature of the material and monotonous teaching methods. This study aims to deeply analyze the influence of using mathematics Puzzle-based Student Worksheets (LKPD) as an innovative learning medium on increasing the learning activeness of second-grade students. The research method employed is a systematic literature review supported by descriptive classroom observation. The review was conducted on more than 20 relevant scientific journal articles indexed in Google Scholar published between 2020 and 2025. The synthesis of the literature indicates that Puzzle media can significantly transform abstract mathematical concepts into concrete and enjoyable activities. This mechanism operates by stimulating intrinsic motivation, enhancing emotional engagement, and creating an interactive learning environment. These findings were validated through direct observation, which showed a tangible increase in activeness indicators, such as the frequency of asking questions, enthusiasm in solving problems, and student interaction. It is concluded that mathematics Puzzle LKPD is an effective pedagogical instrument for increasing the learning activeness of second-grade students, as it bridges the gap between abstract mathematical concepts and the concrete world of children, and changes the perception of learning from an obligation to a challenging game.